Pregnancy-related acute kidney injury leads to hypertension, reduced kidney function and cognitive impairment in postpartum rats - Griffin, Ashley; Szczepanski, Jamie; Spencer, Shauna-Kay; Solis, Lucia; Bowles, Teylor; Robinson, Reanna; Williams, Jan M.; Kyle, Patrick B.; Wallace, Kedra (Frontiers in Physiology, 2024)
IntroductionWomen with hypertensive disorders of pregnancy such as HELLP (hemolysis, elevated liver enzyme, low platelet) Syndrome are affected by acute kidney injury during pregnancy (PR-AKI) at higher rates than women without hypertension. Both hypertensive disorders of pregnancy and Acute Kidney Injury (AKI) outside the context of pregnancy have been associated with an increased risk of developing Chronic Kidney Disease (CKD) and cognitive impairment. In our current study, we set out to determine if PR-AKI led to the development of CKD and impaired cognition in the postpartum period and if HELLP syndrome exacerbates the impairments.MethodsUsing timed-pregnant Sprague Dawley rats, on gestational day (GD) 12, mini-osmotic pumps infusing anti-angiogenic factors were surgically placed in the intraperitoneal cavity to induce HELLP. On GD18, AKI was induced via bilateral renal reperfusion ischemia surgery. Mean arterial pressure and birth outcomes were used to assess the global effects of AKI, and liver enzymes were used to assess HELLP. CKD was assessed by measuring glomerular filtration rate (GFR), urinary output, and renal fibrosis. Anxiety-like behaviors, object recognition memory, spatial memory, and avoidance memory were assessed via behavioral experiments.ResultsHELLP + AKI rats demonstrated more evidence of renal injury, hypertension, and behavioral deficits compared to normal pregnant animals. In addition, AKI had a negative impact on birth outcomes and maternal survival.ConclusionHELLP + AKI together led to evidence of persistent hypertension, progressive renal dysfunction, and cognitive impairment, which were exacerbated compared to AKI or HELLP alone. These findings suggest that PR-AKI in the presence of a hypertensive disorder of pregnancy, such as HELLP, leads to the development of CKD, cognitive dysfunction, and hypertension.